Balancing the Brain: Resting State Networks and Deep Brain Stimulation - Kringelbach, Morten L.; Green, Alex L.; Aziz, Tipu Z. (Frontiers in Integrative Neuroscience, 2011)
Over the last three decades, large numbers of patients with otherwise treatment-resistant disorders have been helped by deep brain stimulation, yet a full scientific understanding of the underlying neural mechanisms is still missing. We have previously proposed that efficacious deep brain stimulation works by restoring the balance of the brain’s resting state networks. Here, we extend this proposal by reviewing how detailed investigations of the highly coherent functional and structural brain networks in health and disease (such as Parkinson’s) have the potential not only to increase our understanding of fundamental brain function but of how best to modulate the balance. In particular, some of the newly identified hub and connectors within and between resting state networks could become important new targets for deep brain stimulation, including potentially in neuropsychiatric disorders. At the same time, it is of essence to consider the ethical implications of this perspective.